2004
DOI: 10.1111/j.1473-6861.2004.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional stereotyping and interprofessional education

Abstract: Effective interprofessional working is considered to be essential for optimum healthcare delivery. Interprofessional rivalry, tribalism and stereotypes are known to exist within healthcare professions and detract from effective health delivery. Limited literature is available that reports undergraduate healthcare students' stereotypical perceptions of each other. Stereotypes in relation to interprofessional education are commonly explained through the Contact Hypothesis Theory, the Realistic Conflict Theory, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 19 publications
2
66
0
11
Order By: Relevance
“…Also, empirical work has indicated that IPE can fail to alter poor stereotypical perceptions of each other (Mandy, Milton and Mandy, 2004). While in another study, there were no significant differences between medical students who had an IPE curriculum and those who had not with regard to their attitudes to collaboration with nurses (Hansson, Foldevi, and Mattsson, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Also, empirical work has indicated that IPE can fail to alter poor stereotypical perceptions of each other (Mandy, Milton and Mandy, 2004). While in another study, there were no significant differences between medical students who had an IPE curriculum and those who had not with regard to their attitudes to collaboration with nurses (Hansson, Foldevi, and Mattsson, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…These range from students holding more positive views about working interprofessionally at the beginning of such programs than when they finished (Mandy et al, 2004;Pollard et al, 2006), to those where students articulated more positive responses at its conclusion (Pollard & Miers, 2008;Smith & Anderson, 2007). Differences between expectations and the realities of experience were evident in most studies.…”
Section: Pedagogical Challenges Of Experiential or Applied Learningmentioning
confidence: 99%
“…Conversely, the key argument for its location in pre-qualifying courses is that students have not been exposed to the socialisation process of their profession or the agency in which they work. Therefore, they do not come to the interprofessional education with stereotypical views of other professions (Herzberg, 1999;Mandy, Milton, & Mandy, 2004).…”
Section: Social Work Participation In Ipe Projectsmentioning
confidence: 99%
“…If a broader definition of competencies is taken that includes student attitudes and knowledge, then several other instances in which competences have been incorporated into evaluations were found. For example, changes in students' attitudes or stereotypes were measured as an IPE learning outcome in several IPE evaluations (Hind et al 2003;Mandy, Milton & Mandy 2004;Hean et al 2006).…”
Section: Behaviourismmentioning
confidence: 99%